2017
DOI: 10.3390/mi8120361
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Assisted Mist Capillary Self-Alignment

Abstract: This paper reports a method combining laser die transfer and mist capillary self-alignment. The laser die transfer technique is employed to feed selected microchips from a thermal release tape onto a receiving substrate and mist capillary self-alignment is applied to align the microchips to the predefined receptor sites on the substrate in high-accuracy. The parameters for a low-power laser die transfer process have been investigated and experimentally optimized. The acting forces during the mist-induced capil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Despite the impressive results achieved so far, it is still challenging to precisely control the spacing of two individual microfibers and the orientation of each microfiber and construct more complex patterns. Previously, our research group has reported a hybrid microassembly technique [21][22][23][24][25] which combines the robotic micro-assembly technique and the surface tension-based self-alignment technique [26][27][28][29][30]. The hybrid microassembly technique has been demonstrated to be able to achieve accurate and fast alignments of microchips, achieving the assembly of 40,000 microchips per hour, with an accuracy higher than 1 µm, and a success rate of 98% [31].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the impressive results achieved so far, it is still challenging to precisely control the spacing of two individual microfibers and the orientation of each microfiber and construct more complex patterns. Previously, our research group has reported a hybrid microassembly technique [21][22][23][24][25] which combines the robotic micro-assembly technique and the surface tension-based self-alignment technique [26][27][28][29][30]. The hybrid microassembly technique has been demonstrated to be able to achieve accurate and fast alignments of microchips, achieving the assembly of 40,000 microchips per hour, with an accuracy higher than 1 µm, and a success rate of 98% [31].…”
Section: Introductionmentioning
confidence: 99%